Strengthening the Understanding of History for Generation Z - Rahman, Abdul; Ima Kesuma, Andi; Junaeda, St.; Dahlan, Mubarak; Najering, Rifal (Society : Jurnal Pengabdian Masyarakat, 2025)
History is the best teacher in life. By learning history, every citizen will have a high love and loyalty to their country. However, it is undeniable that in the midst of global progress, the younger generation, especially the millennials, are exposed to a lack of historical awareness and understanding. Therefore, this activity was designed to provide an in-depth understanding to the millennial generation related to history, especially those related to the history of Makassar City. This activity in the form of a seminar involved the millennial generation from the campus environment, history teachers. After the activity took place, an evaluation was carried out by asking questions directly to the younger generation regarding this activity. In general, they were enthusiastic about this activity and have an understanding that Makassar City today has a longhistorical dynamic.